1981
DOI: 10.1111/j.1432-1033.1981.tb05171.x
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Ribosomal RNA Transcription in Lymphocytes. Evidence that the Rate of Chain Elongation Is the Limiting Factor

Abstract: During activation of lymphocytes by phytohaemagglutinin, the nuclear activity of RNA polymerase I increases with no proportional increase in the amount or catalytic efficiency of the enzyme in the cell. The mechanism by which rRNA transcription in lymphocytes is modified by phytohaemagglutinin stimulation was investigated. The following results were obtained. (a) In resting lymphocytes all RNA polymerase I1 molecules are bound to the template while a pool of excess free RNA polymerase I, not engaged in transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Despite the emphasis that until recently was placed on initiation as a means of regulating rRNA gene transcription, several early studies suggested that the capacity of RPI to initiate does not explain growth regulation in vivo [154,[182][183][184]. Most telling, however, are the Miller spread observations of tightly packed transcription complexes along the coding regions of the rRNA genes (Fig.…”
Section: Regulating the Rrna Transcription Elongation Ratementioning
confidence: 94%
“…Despite the emphasis that until recently was placed on initiation as a means of regulating rRNA gene transcription, several early studies suggested that the capacity of RPI to initiate does not explain growth regulation in vivo [154,[182][183][184]. Most telling, however, are the Miller spread observations of tightly packed transcription complexes along the coding regions of the rRNA genes (Fig.…”
Section: Regulating the Rrna Transcription Elongation Ratementioning
confidence: 94%
“…This result suggests that alterations in the rate of rRN A production are mediated largely by changes in the rate of transcriptional initiation. The alternative possibilities, that rRNA production may be regulated primarily by changes in rRNA stability or in the rate of elongation, appear unlikely although these may be contributing factors in certain situations (172)(173)(174)(175).…”
Section: Regulation Of Rdna Transcriptionmentioning
confidence: 98%
“…Template-dinucleotide primer pairs are: a) poly(dA)-poly(dT) + ApA (1), poly(dT) + ApA (2), poly(dA)-poly(dT) + UpU (3), poly(dA) + UpU (4). b) poly(dC) + GpG (1), poly(dC)-poly(dG) + GpG (2).…”
Section: Nucleosi Triphshatesu Rate Ki Neti Csunclassified
“…However, recent results illustrate the possible importance of other steps in eucaryotic transcription. Thus Dauphinais (2) suggested that, rDNA transcription during lymphocyte activation might be controlled at the level of the elongation reaction. Studies conducted with plant RNA polymerases II also suggest that the elongation-translocation properties of the enzymes could depend on the nucleotide sequence (and/or conformation) of the DNA sequence being transcribed.…”
Section: Introductionmentioning
confidence: 99%